Lipase-Catalyzed Baeyer-Villiger Oxidation of Cellulose-Derived Levoglucosenone into (S)-γ-Hydroxymethyl-α,β-Butenolide: Optimization by Response Surface Methodology - Teixeira, Andreia R. S.; Flourat, Amandine L.; Peru, Aurelien A. M.; Brunissen, Fanny; Allais, Florent (Frontiers in Chemistry, 2016)
Cellulose-derived levoglucosenone (LGO) has been efficiently converted into pure (S)-gamma-hydroxymethyl-alpha,beta-butenolide (HBO), a chemical platform suited for the synthesis of drugs, flavors and antiviral agents. This process involves two-steps: a lipase-catalyzed Baeyer-Villager oxidation of LGO followed by an acid hydrolysis of the reaction mixture to provide pure HBO. Response surface methodology (RSM), based on central composite face-centered (CCF) design, was employed to evaluate the factors effecting the enzyme-catalyzed reaction: pka of solid buffer (7.2 - 9.6), LGO concentration (0.5 - 1 M) and enzyme loading (55 - 285 PLU.mmol-1). Enzyme loading and pka of solid buffer were found to be important factors to the reaction efficiency (as measured by the conversion of LGO) while only the later had significant effects on the enzyme recyclability (as measured by the enzyme residual activity). LGO concentration influences both responses by its interaction with the enzyme loading and pka of solid buffer. The optimal conditions which allow to convert at least 80% of LGO in 2 hours at 40 °C and reuse the enzyme for a subsequent cycle were found to be: solid buffer pka = 7.5, [LGO] = 0.50 M and 113 PLU.mmol-1 for the lipase. A good agreement between experimental and predicted values was obtained and the validity of the model confirmed (p-value 0.05).